Membangun Strategi Koneksi Emosional Pelanggan Pada Counter Siti Cell Di Tangerang - Pangesti, Nisa Ayu; Syahrinullah, Syahrinullah (Journal of Management Branding, 2025)
This research was conducted to analyze the right strategies to build emotional relationships with customers. Therefore, we need a strategy to maintain customer loyalty . The purpose of this study is to build an emotional connection strategy at Counter Siti Cell in Tangerang, in order to increase loyalty satisfaction and maintain customer loyalty. This research uses a literature study approach that collects and analyzes information from various academic journals and books relevant to the topic of emotional marketing. This research method was chosen because it can provide a deep understanding of the approach strategy carried out by this credit counter and its impact on increasing sales. The results of the study show that: building a customer emotional relationship connection strategy at Counter Siti Cell in Tangerang is by implementing a product warranty policy, appreciating and accepting criticism and suggestions from customers, honestly explaining the personality of the product with details of its advantages and disadvantages, paying attention to stakeholders and having good conversations, so as to create customer satisfaction with their trust in the company